Can match running performance be affected by an improvement in maximal aerobic speed? - Simpson, B.; Buchheit, M.; Al Haddad, H.; Mendez-Villanueva, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Aerobic capacity is thought to be an essential quality for successful participation in soccer. Data from cross-sectional studies suggest that position-dependent correlations may exist between maximal performance in incremental tests (i.e., maximal aerobic speed, MAS) and very high intensity activities during soccer matches (VHIA) (Buchheit et al., 2010; Mendez-Villanueva et al, 2012). However, there is very limited data on longitudinal changes in MAS and their effect on VHIA. Therefore, and the aim of the present study was to examine, in highly-trained soccer players, whether substantial improvements in MAS can translate to improved VHIA. Methods: Seventeen highly-trained youth male soccer players (age: 14.1 ± 0.8y; height: 164.9 ± 6.3cm) were selected based on data eligibility (i.e., players that showed substantial increases (greater than CV) in MAS between two consecutive testing periods) and have played a minimum of 2 international club games within 1-2 months from/to each testing period. Time-motion analyses were performed using a global positioning system (1-Hz). VHIA were calculated as running speed >16.1km/h. Results: Substantial improvements in MAS were associated with a small increase in VHIA for full backs (ES = 0.35, 90%CI (0.09; 0.61)), small decrease in centre backs (ES = -0.51, 90% CI (-1.00; -0.01)) and no changes in midfielders and wingers (ES = 0.03 & 0.10, 90% CI (-0.45; 0.51) & (-0.30; 0.50), respectively). Discussion: We found that improved MAS may not have a direct impact on high-intensity match running performance. One must consider the fine interaction between tactical, technical and psychological components. Our results confirm that playing structure (e.g., tactical choices) has an important role in influencing the expression of MAS during soccer match play, and hence, match running performance (Buchheit et al., 2010; Mendez-Villanueva et al, 2012).